EVALUASI PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS RUKUN WARGA KELURAHAN TANJUNG RHU KOTA PEKANBARU - Parasian Manurung; Zaili Rusli; Dadang Mashur (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
This research is to find out and analyze the evaluation results of the community empowerment program based on the pillars of the community (PMB-RW) in the Tanjung Rhu Village and the inhibiting factors for the evaluation of the PMB-RW program in the Tanjung Rhu Village. This study uses a qualitative research method with a case study approach that is descriptive in nature through the process of collecting interview data, observation, and document study. The results showed that the evaluation of the PMB-RW program had not been carried out properly and maximally and that PMB-RW had not been able to handle and reduce the poverty rate in Tanjung Rhu Village. Evaluation of the context of the PMB-RW program has not been in accordance with the plan, has not been able to analyze the background of the implementation of PMB-RW and difficulties in achieving goals. Evaluation of the input of the PMB-RW program has not been able to utilize existing resources and the identification of resources has not been maximized.